Faculty case studies on learning to teach inclusively in undergraduate STEM education - Hill, Lucas B.; Buchanan, Diamond; Woods, Sara E.; Frey, Regina F. (Frontiers in Education, 2025)
IntroductionThis study aimed to understand how STEM faculty members developed as inclusive instructors after completing a free, high-engagement, inclusive teaching development program. The Inclusive STEM Teaching Project (ISTP), a Massive Online Open Course (MOOC), provides participants with five modules and additional learning opportunities that dig deep into instructor and student identity, classroom climate, and diversity, equity, and inclusion (DEI) in higher education.MethodsWe conducted nine, mixed methods in-depth case studies with faculty member course participants across the U.S. and various STEM disciplines.Results and discussionResults demonstrated iterative growth incorporating instructor identities in cognitive, affective, confidence, and behavioral outcomes. The paper concludes with a conceptual framework that showcases the development of inclusive instructors in higher education.